Aberrant expression of the microRNA cluster in 14q32 is associated with del(5q) myelodysplastic syndrome and lenalidomide treatment - Krejčík, Zdeněk; Beličková, Monika; Hruštincová, Andrea; Kléma, Jiří; Zemanová, Zuzana; Michalová, Kyra; Čermák, Jaroslav; Jonášová, Anna; Dostálová Merkerová, Michaela (Cancer genetics, 2015)
Lenalidomide is a novel thalidomide analogue with immunomodulatory and antiangiogenic effects that has been successfully used for the treatment of low and intermediate-1 risk myelodysplastic syndromes (MDSs) with a del(5q) aberration. Because information about the influence of lenalidomide on the microRNA (miRNA) transcriptome is limited, we performed miRNA expression profiling of bone marrow CD34+ cells obtained from MDS patients with the del(5q) abnormality who had been subjected to lenalidomide treatment. To define differences in miRNA expression, we performed paired data analysis to compare the miRNA profiles of patients before and during lenalidomide treatment and those of healthy donors. The analysis showed that miRNAs clustering to the 14q32 region had a higher expression level in patient samples before treatment than in the healthy control samples, and this elevated expression was diminished following lenalidomide administration. Because some of the 14q32 miRNAs play important roles in hematopoiesis, stem cell differentiation, and apoptosis induction, the expression of this cluster may be associated with the pathophysiology of the disease.
Keywords: chromozomální delece; regulace genové exprese u nádorů; sekvenční delece; Oligonucleotide Array Sequence Analysis; thalidomid; Thalidomide; del(5q); Chromosomes, Human, Pair 14; Gene Expression Regulation, Neoplastic; 14q32; imunologické faktory; lenalidomid; lidé; Angiogenesis Inhibitors; inhibitory angiogeneze; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Lenalidomide; studie případů a kontrol; lidské chromozomy, pár 14; stanovení celkové genové exprese; Myelodysplastic Syndromes; myelodysplastické syndromy; Immunologic Factors; Case-Control Studies; Chromosome Deletion; mikro RNA; miRNA; Chromosomes, Human, Pair 5; MicroRNAs; Sequence Deletion; myelodysplastic syndrome; lenalidomide; Gene Expression Profiling; lidské chromozomy, pár 5; Humans